PENGARUH TIME PRESSURE, AUDIT RISK, PROFESSIONAL COMMITMENT, REVIEW PROCEDURE AND QUALITY CONTROL DAN SELF ESTEEM IN RELATION TO AMBITION TERHADAP TERJADINYA PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT(PREMATURE SIGN OFF) (Studi Empiris pada Kantor Akuntan P - Sitorus, Santa Ulina; ', Zirman; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study examines the influence of time pressure, audit risk, professional commitment, review procedure and quality control and self esteem in relation to ambition to premature sign-off of audit procedure of Public Accountant Firms. Respondents in this study are auditors who worked for public accounting firm in Riau, Padang, Medan. The samples in this study are 120 auditors from 30 public accounting firms. The method of determining the sample is by using purposive sampling method, while the data processing methods used by researcher are the multiple regression and use SPSS version 17.00 as the software for processing the data. The result shows that the time pressure, audit risk, positively and significantly influences to premature sign-off of audit procedure. Professional commitment, review procedure and quality control and self esteem in relation to ambiton, negatively and significantly influences to premature sign-off of audit procedure.Keyword: Time Pressure, Professional Commitment, Review Procedure and Quality Control, Self Esteem in Relation to Ambition and Premature Sign-Off of Audit Procedure.